Imagens geopoéticas em vidas secas: travessias da literatura ao cinema - Mota Junior, Raimundo Borges da (2021)
In this work, we seek to present a reading of images in Vidas seca da literature (1938), by Graciliano Ramos and Vidas seca do Cinema (1963), by Nelson Pereira dos Santos, through a look at the crossing of the literary text to the cinematographic. It is a comparative study, permeated with critical perspectives from Geopoetics, which seeks to present aspects of the landscape and imagery fields in the narratives of these works, which are set in a space that reconfigures the real to illustrate a neo-realist narrative landscape, but also reconstructs the meanings of the characters and of the recurring cyclical imagery in traditional backwoods geopoetics. The understanding of Geopoetics encompasses the discursive fields that move between the literary, the philosophical, the political and other references. Thus, this study has a qualitative character, thus addressing the environmental aspects expressed in landscapes and fictional images in crossings in the dialogue between the two works. To conceptualize this dissertation, we have main authors, such as: Avellar (2007) Aumont (1993); Bouvet (2012); Debs (2010); Santos (1996); Souza (2009) and White (s.d), in addition to other complementary references, which make it possible in this study to establish an assertive dialogue between Literature and Cinema, mobilizing geographical and historical references in discussions about the landscape and imagery aspects of the studied artistic productions. It can be noted, then, with the results obtained, the manifestation of geopoetic expressions in the verbal and visual construction of the literary and filmic landscapes, respectively, which is capable of boosting even more readings and researches of these acclaimed works of literary and cinematographic arts in Brazil.